The Impact Of Financial Risks On Banking Performance: Study On Al-Wahda Bank- Benghazi - عبد اللطيف الشيخي فاطمة; محمد العريبي حواء (Dirasat in Economics and Business, 2024)
This study aimed at liquidity and credit risks with the aim of assessing the impact of these financial risks on banking performance. The participants in the study is consisted of employees in the risk management of Al-Wahda Bank in Benghazi. A questionnaire was designed and distributed to 40 employees and staff in departments identified for this study, 34 questionnaires were retrieved, while 30 were suitable for analysis, resulting in a response rate of approximately 75%.These data were analyzed using stepwise multiple inclination and correlation coefficient (Pearson). The study found that the strongest correlation was between the degree of impact of liquidity risks and banking performance. These were the two pivotal factors. Conversely, the weakest correlation observed was between the degree of impact of credit risks and banking performance, which means that the bank’s performance have a great impact on liquidity risks. The study recommended investigating the impact of other financial risks, including market risks, operational risks, counterparty risks, sovereign risks, reputational risks, regulatory and compliance risks, and safety risks.